The Effect Of Epoxy Resin Ratio And Sugar Cane Bagasse Particle Dimensions On The Effectiveness Of Noise-Reducing Materials - Adhi Purna Yulian Putra; Anas Mukhtar; Gatut Rubiono; Muhamad Khoirul Anam; Adi Pratama Putra (Journal of Educational Engineering and Environment, 2026)
: Noise is a sound pollution that has a significant impact on human health and the environment. The use of bagasse waste as a noise dampener is an interesting alternative material source to be developed. This study aims to determine the effect of the ratio of epoxy resin and particle dimensions of bagasse waste on the effectiveness of noise dampening materials. The study was conducted experimentally, where the composite was made using variations in the ratio of epoxy resin to bagasse, namely: 10:40, 10:50, and 10:60 grams. Bagasse particle powder used three different mesh sizes, namely 16, 20, and 30. Testing the sound absorption capacity of the dampening specimen was carried out using a PVC impedance tube with a length of 100 cm and a diameter of 15 cm, the sound source used a frequency of 50 Hz–1000 Hz with the specimen placed at a distance of 50 cm and 75 cm from the sound source. The results showed that the ratio of epoxy resin and particle dimensions of bagasse affected the reduction of noise levels. The increase in the ratio of epoxy resin and bagasse powder is directly proportional to the composite density value, where the highest density value of 0.78 g/cm³ is obtained at a composition of 10:60 grams at a mesh size of 20, while the lowest density is 0.54 g/cm³ at a composition of 10:40 grams mesh 16. The most optimal sound absorption coefficient is achieved at a mixture ratio of 10:60 grams mesh 30 with an effectiveness of 10% at a distance of 50 cm from the noise source.